2011
DOI: 10.1088/0004-637x/730/1/55
|View full text |Cite
|
Sign up to set email alerts
|

The Arecibo Methanol Maser Galactic Plane Survey. Iv. Accurate Astrometry and Source Morphologies

Abstract: We present accurate absolute astrometry of 6.7 GHz methanol masers detected in the Arecibo Methanol Maser Galactic Plane Survey using MERLIN and the Expanded Very Large Array (EVLA). We estimate the absolute astrometry to be accurate to better than 15 and 80 milliarcseconds for the MERLIN and EVLA observations respectively. We also derive the morphologies of the maser emission distributions for sources stronger than ∼ 1 Jy. The median spatial extent along the major axis of the regions showing maser emission is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
77
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 33 publications
21
77
0
Order By: Relevance
“…a halo structure that surrounds the core of the masers. Moreover, if the maser spots do not have a compact core, they would not be detected in the EVN observations (Pandian et al 2011). Although in our observations the EVN resolves out about 50% of the flux of group C (V lsr > −61 km s −1 ), the majority of the flux appears to be recovered across the entire CH 3 OH maser spectrum.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…a halo structure that surrounds the core of the masers. Moreover, if the maser spots do not have a compact core, they would not be detected in the EVN observations (Pandian et al 2011). Although in our observations the EVN resolves out about 50% of the flux of group C (V lsr > −61 km s −1 ), the majority of the flux appears to be recovered across the entire CH 3 OH maser spectrum.…”
Section: Discussionmentioning
confidence: 51%
“…This slight difference can be explained by the different resolution of the two instruments and flux calibration uncertainties in the Effelsberg observations (∼10%, Vlemmings 2008). This means that no significant changes occurred between the two epochs and there is no indication of a core/halo structure of the maser features (hereafter simply called masers) at scales of ∼100 AU such as described for a sample of CH 3 OH maser sources by Pandian et al (2011).…”
Section: Discussionmentioning
confidence: 97%
“…VLBI observations of G45.473+0.134 in March 2010 have shown that the maser emission comes from three clusters . No significant changes in morphology were seen as compared with the maps obtained in 2007 with MER-LIN (Pandian et al 2011). Comparison of the spectra taken with the 32 m telescope and VLBI indicates that less than 15 per cent of the flux density was missed in the VLBI observation figure A1), thus the source morphology is accurately recovered.…”
Section: Size Of Maser Region Showing Periodic Variabilitymentioning
confidence: 76%
“…We plot the distribution of young stellar objects (YSOs as dotted black curve) from the RMS survey (Hoare et al 2005), CH 3 OH masers from Pandian et al (2011), Szymczak et al (2002), and Caswell et al (2010 (dashed and dashed-dotted curves) and the ATLASGAL sample as a solid curve in green in the middle panel. The YSOs are MSX sources (Price et al 2001), which emit at infrared wavelengths and are therefore in a more evolved phase than the IRDCs.…”
Section: Temperature and Linewidth Distributions In Different Evolutimentioning
confidence: 99%